Pengembangan Game 2D Platformer Berbasis Microbit Menggunakan Unity - Saputra, Rizqi Kurniawan; Setiawan, Kiki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to develop a 2D platformer game using the Microbit platform and Unity as the development tools. The Microbit serves as the controller with various sensors and computational capabilities. The development process starts with designing the game concept, including level design, characters, and mechanics. Unity is used to create levels, game logic, and connect the Microbit to the game. Users can control the character through the sensors and buttons on the Microbit. Testing involves participants to measure the game's quality and effectiveness and gather feedback. The collected data is used to analyze the strengths and weaknesses of the game and make iterations to enhance the gaming experience. As a result, the researchers have created a game that can be controlled via Microbit, enriching the gaming experience.